AI-assisted language education: critical review (Educational Dimension, 2021)
This paper reviews the current research on AI-assisted language education (AILE). AI has greatly influenced education, especially language learning. AILE, an interdisciplinary field combining AI technology and language education theory, aims to improve foreign language learners’ experiences through personalized, interactive, and collaborative learning. This review classifies AILE research into four key domains: language-specific applications, comprehensive teaching modes, new educational ecosystems, and identification technology integration. It analyzes the strengths, weaknesses, opportunities, and challenges of AILE. The paper emphasizes the importance of ethical considerations and data quality in AILE endeavors. While acknowledging the achievements and potential of AILE, the review suggests future directions, promotes interdisciplinary collaboration, and highlights the need for empirical studies for an effective and ethical integration of AI in language education.